Educação ambiental: o jogo didático como ferramenta de ensino no zoológico - Barros, Jéssyca Danieli (Universidade Federal de São Carlos, 2017)
Environments such as zoos are becoming less visited, especially by children and young people. It is important, therefore, for zoos to seek more interactive activities, such as educational games, which can provide a more ludic and enjoyable experience, and serve as a tool in Environmental Education. Thus, the objective of this study was to develop an educational game as a facilitating tool for teaching and learning about some species of animals present in the Zoológico Municipal Engenheiro Cid Almeida Franco (PEMA, Americana, SP), based on the card game Super Trunfo® (Grow Jogos e Brinquedos Ltda.). A bibliographic survey of more than 400 species present was conducted, and 32 were selected based on the following criteria: i) the degree of threat of extinction; ii) whether the animals are exotic; and iii) species that do not have characteristics known to the general public. After this stage, periodic visits were made to the enclosures to observe the animals in captivity and obtain photographs. The material developed was called "Zoo Cards - The Animal Super Trunfo," and the adopted characteristics were weight, development, litter size, longevity, and threat of extinction. The game accommodates two to eight participants, is rated for all ages, and can be played by any literate person. Additionally, it will be available for download (free access) and printing on the PEMA website (https://www.researchgate.net/publication/361265721_Zoo_Cards_-_manualpdf) and (https://www.researchgate.net/publication/361265499_Zoo_Cards_-_cartaspdf). To assess the quality of the material produced, a questionnaire was administered to a group of 15 participants, whose responses followed the Likert scale. Overall, "Zoo Cards" received a good evaluation, mainly for being a fun activity that involves the cooperation/competition relationship in an educational context, making the teaching and learning process more comprehensive and interactive. Zoos have a significant influence on connecting people with nature and are vital for building support for preservation. The educational game, in this context, can be an important agent, engaging visitors in preservation behaviors and respect for biodiversity.
Environmental education: the didactic game as a teaching tool in the zoo
Keywords: Parque Ecológico de Americana; Ensino-aprendizagem; Lúdico; Preservação; Americana ecological park; Teaching-learning; Ludic; Conservation; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS